2009
DOI: 10.3855/jidc.126
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum AmpC and metallo-beta-lactamases in Serratia and Citrobacter spp. in a disc approximation assay

Abstract: Objectives: This study aimed to develop a novel model for detection of extended spectrum beta-lactamase (ESBL), AmpC and metallo-betalactamase (MBL) producing Serratia and Citrobacter species using cefoperazone sulbactam as well as other inducer-substrate combinations in a disc approximation assay. In the absence of molecular tools in developing countries, we attempted to standardize simple phenotypic techniques for detection of beta-lactamases to allow effective patient care in our countries. These techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…In a study from India of isolates recovered from different types of clinical specimens from 2007 to 2008, 25.6% of Serratia isolates produced AmpCs, 40% of which were inducible, and 60% of these isolates were derepressed mutants. Besides S. marcescens, the authors did not identify the isolates to the species level (321).…”
Section: ␤-Lactam Resistance In Serratia Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study from India of isolates recovered from different types of clinical specimens from 2007 to 2008, 25.6% of Serratia isolates produced AmpCs, 40% of which were inducible, and 60% of these isolates were derepressed mutants. Besides S. marcescens, the authors did not identify the isolates to the species level (321).…”
Section: ␤-Lactam Resistance In Serratia Speciesmentioning
confidence: 99%
“…A survey of S. marcescens isolates from 2006 to 2009 in Mexico revealed that 20.5% were ESBL producers, and all of the ESBLs were SHV-type enzymes (143). In India, Rizvi and others found that 33% of Serratia species recovered from various clinical specimens from 2007 to 2008 were ESBL producers; they did not determine the type of enzymes present and did not report which species of Serratia were present besides S. marcescens (321).…”
Section: ␤-Lactam Resistance In Serratia Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in a diameter of 5 mm was considered positive for ESBL detection. 7 Detection of inducible and derepressed AmpC betalactamase: Isolates resistant to ceftriaxone, cefixime, cefoperazone and cefoperazone-sulbactam were tested for AmpC production. Organism resistant to cefoperazone and cefoperazone-sulbactam combination were considered AmpC producers.…”
Section: Detection Of Esblmentioning
confidence: 99%
“…There are several screening tests for detection of MBL production but no single test when used alone is specific for the same. 13 Rizvi et al 29 found DDST using EDTA better than Hodge test. Lee K et al also found that Hodge test was a simple screening method for MBL producing isolates, but occasional isolates showed false negative result.…”
Section: Resultsmentioning
confidence: 99%